A Proposal for the retrospective identification and categorization of older people with functional impairments in scientific studies: recommendations of the Medication and Quality of Life in Frail Older Persons (MedQoL) Research Group - Brefka, Simone; Haefeli, Walter E.; Bauer, Jürgen M. (Journal of the American Medical Directors Association, 2019)
When treating older adults, a main factor to consider is physical frailty. Because specific assessments in clinical trials are frequently lacking, critical appraisal of treatment evidence with respect to functional status is challenging. Our aim was to identify and categorize assessments for functional status given in clinical trials in older adults to allow for a retrospective characterization and indirect comparison of treatment evidence from these cohorts. We conducted 4 separate systematic reviews of randomized and nonrandomized controlled clinical trials in older people with hypertension, diabetes, depression, and dementia. All assessments identified that reflected functional status were analyzed. Assessments were categorized across 4 different functional status levels. These levels span from functionally not impaired, slightly impaired, significantly impaired, to severely impaired/disabled. If available from the literature, cut-offs for these 4 functioning levels were extracted. If not, or if the existing cut-offs did not match the predefined functional levels, cut-off points were defined by an expert group composed of geriatricians, pharmacists, pharmacologists, neurologists, psychiatrists, and epidemiologists using a patient-centered approach. We identified 51 instruments that included measures of functional status. Although some of the assessments had clearly defined cut-offs across our predefined categories, many others did not. In most cases, no cut-offs existed for slightly impaired or severely impaired older adults. Missing cut-offs or values to adjust were determined by the expert group and are presented as described. The functional status assessments that were identified and operationalized across 4 functional levels could now be used for a retrospective characterization of functional status in randomized controlled trials and observational studies. Allocated categories only serve as approximations and should be validated head-to-head in future studies. Moreover, as general standard, upcoming studies involving older adults should include and explicitly report functional impairment as a baseline characteristic of all participants enrolled.
Gesehen am 29.03.2019